Practicing Level and Determinants of Safe Cord Care and Skin-To-Skin Contact Among Post-partum Women in Public Hospitals of Eastern Ethiopia - Eyeberu, Addis; Getachew, Tamirat; Debella, Adera; Birhanu, Abdi; Alemu, Addisu; Dessie, Yadeta (Frontiers in Pediatrics, 2022)
Background: Despite the fact that practicing levels of cord care and skin-to-skin contact among postpartum women are critical to reducing neonatal deaths, limited data revealed low practicing. Thus, the purpose of this study was to determine the level of practice and determinants of cord care and skin-to-skin contact among postpartum women in public hospitals of Eastern Ethiopia. Methods: A facility-based cross-sectional study was employed at the public hospitals of eastern Ethiopia. A random sample of 820 postpartum women was included in the study. A pre-tested and structured questionnaire was used to collect data through a face-to-face interview. STATA version 14 was used for data analysis. Bivariate and multivariate logistic regression analyses were employed to determine the association between independent variables and outcome variables. Results: The practicing level of cord care was 71.7% (95% CI: 64.5, 81.7). While the practicing level of Skin-to-Skin contact was 53.2% (95% Confidence interval:43.6, 58.8). Age of mothers [adjusted odds ratio =2.93, 95% Confidence interval:1.24, 6.96], educational status [adjusted odds ratio=1.83, 95% Confidence interval (1.08, 3.13)], and knowledge of postpartum women on cord care [adjusted odds ratio =11.3, 95% Confidence interval: (7.49, 17.18)] were determinants of cord care practice. Conclusions: When compared studies, the practicing level of cord care and skin-to-skin contact was high. In this study, the age of mothers, educational status, and knowledge of postpartum women on cord care were determinants of cord care practice. while the age of mothers, marital status, occupational status, and gestational age at birth were significantly associated with skin-to-skin contact practice. Clean cord care should be strengthened and intensified to reduce neonatal mortality due to avoidable umbilical cord infections. Furthermore, skin-to-skin contact practice should be strengthened to enhance the survival of at-risk neonates.